Longitudinal optimal analytical midcourse guidance for cruise-glide integrated hypersonic vehicles - Xin Li; Guangbin Cai; Hui Xu; Jianwen Zhu; Chaoxu Mu (Defence Technology)
For the longitudinal midcourse guidance problem of a cruise-glide integrated hypersonic vehicle (CGHV), an analytical method based on optimal control theory is proposed. This method constructs a guidance dynamics model for such vehicles, using aerodynamic load as the control variable, and introduces a framework for solving the guidance laws. This framework unifies the design process of guidance laws for both the glide and cruise phases. By decomposing the longitudinal guidance task into position control and velocity control, and minimizing energy consumption as the objective function, the method provides an analytical solution for velocity control load through the calculation of costate variables. This approach requires only the current state and terminal state parameters to determine the guidance law solution. Furthermore, by transforming path constraints into aerodynamic load constraints and solving backwards to obtain the angle of attack, bank angle, and throttle setting, this method ensures a smooth transition from the glide phase to the cruise phase, guaranteeing the successful completion of the guidance task. Finally, the effectiveness and practicality of the proposed method are validated through case simulations and analysis.